Nonlinear Approaches in Engineering Applications Energy, Vibrations, and Modern Applications - Dai, Liming; Jazar, Reza N.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book analyzes the updated principles and applications of nonlinear approaches to solve engineering and physics problems. The knowledge on nonlinearity and the comprehension of nonlinear approaches are inevitable to future engineers and scientists, making this an ideal book for engineers, engineering students, and researchers in engineering, physics, and mathematics. Chapters are of specific interest to readers who seek expertise in optimization, nonlinear analysis, mathematical modeling of complex forms, and non-classical engineering problems. The book covers methodologies and applications from diverse areas such as vehicle dynamics, surgery simulation, path planning, mobile robots, contact and scratch analysis at the micro and nano scale, sub-structuring techniques, ballistic projectiles, and many more. Explores the nonlinear approaches that open avenues to better, safer, cheaper, and more cost-effective consumption of power and raw materials; Exposes readers to a broad range of practical topics and approaches; Contains a strong emphasis on application, physical meaning, and the methodologies of the approaches discussed.
Section 1: Energy Applications.- Nonlinear Behaviour Diagnosis for Horizontal Axis Wind Turbine Blades Subjected to Inconstant Wind Excitations.- Concentrated solar power plants capacity factors: A review.- Section 2: Vibrations and Automotive Applications.- Vibration Analysis of Oscillators with Generalized Inertial and Geometrical Nonlinearities.- Quarter Car Suspension Model with Provision for Loss of Contact with The Road.- Friction Coefficient of Pneumatic Tires and Bitumen Roads.- Solutions for Path Planning using Spline Parameterization.- Section 3: Modern Engineering Applications.- Diagnosis of nonlinear stochastic dynamics of active slider in nanometer spacing.- Formation Control of Nonholonomic Mobile Robots using an Acoustic Sensor.- Nonlinear Size-dependent Instability of Hybrid FGM Nanoshells -- Section 4: Analytical-Numerical Analysis Applications.- An exact solution technique for impact oscillators.- A semi-analytical solution for bending of nonlinear magnetostrictive beams.- Limted Data Modelling Approaches for Engineering Applications.- Theoretical and Numerical Investigation of The Elastic-Plastic Behavior of Thick-walled Cylinders.- A Complex Variable Method to Predict an Aerodynamics of Arbitrary Shape Ballistic Projectiles.- Extension of substructuring technique in the nonlinear domain -- Index.
Keywords: Dynamics; Nonlinear theories; Multibody systems; Vibration; Mechanics, Applied; System theory; Nonlinear Optics; Applied Dynamical Systems; Multibody Systems and Mechanical Vibrations; Complex Systems; Nonlinear Optics